Profiling of fine- and coarse-mode particles with LIRIC (LIdar/Radiometer Inversion Code) - PERRONE, Maria Rita; BURLIZZI, PASQUALE; DE TOMASI, Ferdinando; A. Chaikovsky (Copernicus Publications, 2014)
The paper investigates numerical procedures that allow determining the dependence on altitude of aerosol properties from multi wavelength elastic lidar signals. In particular, the potential of the LIdar/Radiometer Inversion Code (LIRIC) to retrieve the ver- 5 tical profiles of fine and coarse-mode particles by combining 3-wavelength lidar measurements and collocated AERONET (AErosol RObotic NETwork) sun/sky photometer measurements is investigated.